DESAIN DAN FABRIKASI SISTEM OTOMATISASI KONTROL PADA SISTEM HIDROPONIK NUTRISI BERBASIS ARDUINO - M. Fadli Solehudin; Kusmiyati; Oscar Haris (Jurnal Mema (Jurnal Mesin dan Manufaktur), 2026)
Hydroponics is a soilless cultivation method that utilizes nutrient solutions as the primary source of plant nutrients. One of the most critical factors in hydroponic cultivation is maintaining nutrient concentration according to plant requirements at each growth stage. This study aims to design, fabricate, and evaluate an Arduino-based automated nutrient control system for hydroponic applications. The research employed the Research and Development (R&D) method, which included mechanical design, control system design, microcontroller programming, fabrication, and system testing. The developed system consists of an Arduino Uno as the main controller, an Electrical Conductivity (EC) sensor for nutrient concentration measurement, a peristaltic pump as the nutrient dosing actuator, a relay module, a Real Time Clock (RTC), and an LCD I2C display for real-time monitoring. System performance was evaluated by comparing EC sensor readings with a reference TDS/EC meter at several nutrient setpoints. The results demonstrated that the system was capable of automatically supplying nutrient solution according to the predefined setpoints. The maximum difference between the EC sensor readings and the TDS/EC meter measurements was 43 ppm, indicating satisfactory accuracy for hydroponic nutrient control applications. Therefore, the proposed system has the potential to improve nutrient management efficiency and support the implementation of smart farming technologies in hydroponic cultivation.